Assessing differences in inhaled corticosteroid response by self-reported race-ethnicity and genetic ancestry among asthmatic subjects - Wells, Karen E.; Cajigal, Sonia; Peterson, Edward L.; Ahmedani, Brian K.; Kumar, Rajesh; Lanfear, David E.; Burchard, Esteban G.; Williams, L. Keoki (Journal of allergy and clinical immunology, 2016)
Inhaled corticosteroids (ICSs) are the preferred treatment for achieving asthma control. However, little is known regarding the factors contributing to treatment response and whether treatment response differs by population group. We sought to assess behavioral, sociodemographic, and genetic factors related to ICS response among African American and European American subjects with asthma. Study participants were part of the Study of Asthma Phenotypes and Pharmacogenomic Interactions by Race-ethnicity (SAPPHIRE). The analytic sample included asthmatic subjects aged 12 to 56 years with greater than 12% bronchodilator reversibility and percent predicted FEV1 of between 40% and 90%. Participants received 6 weeks of inhaled beclomethasone dipropionate. The primary measure of ICS response was a change in Asthma Control Test (ACT) score; the secondary measure was a change in prebronchodilator FEV1. Adherence was measured with electronic monitors. Genetic ancestry was estimated for African American participants by using genome-wide genotype data. There were 339 study participants; 242 self-identified as African American and 97 as European American. Baseline ACT score, percent predicted FEV1, degree of bronchodilator response, and ICS adherence were significantly associated with ICS response. A baseline ACT score of 19 or less was useful in identifying those who would respond, as evidenced by the significant dose-response relationship with ICS adherence. Neither self-reported race-ethnicity among all participants nor proportion of African ancestry among African American participants was associated with ICS responsiveness. Our findings suggest that baseline lung function measures and self-reported asthma control predict ICS response, whereas self-reported race-ethnicity and genetic ancestry do not.